2018
DOI: 10.1016/j.aucc.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

After-hours respiratory physiotherapy for intubated and mechanically ventilated patients with community-acquired pneumonia: An Australian perspective.

Abstract: Further research is required to determine whether the frequency of respiratory physiotherapy intervention, including after-hours provision of treatment, influences outcomes for ICU patients intubated with pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…There is variability in the provision of after-hours cardiopulmonary physical therapy (care provided after normal work hours, e.g., 5 PM-8 AM, which may include variations of late shifts, overnight shifts, and/or on-call), with 79% in the United Kingdom; 0% in Germany, Portugal, and Sweden; and 47% in Australia, of acute hospitals having an after-hours service. 5,16,17 Guidelines and standards are just evolving for the educational profile and scope of practice requirements for physical therapy within ICUs in Australia, Japan, Nigeria, Singapore, the United Kingdom, and South Africa. [18][19][20][21][22][23][24] However, it is unclear whether hospital physical therapy or critical care departments utilize these guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…There is variability in the provision of after-hours cardiopulmonary physical therapy (care provided after normal work hours, e.g., 5 PM-8 AM, which may include variations of late shifts, overnight shifts, and/or on-call), with 79% in the United Kingdom; 0% in Germany, Portugal, and Sweden; and 47% in Australia, of acute hospitals having an after-hours service. 5,16,17 Guidelines and standards are just evolving for the educational profile and scope of practice requirements for physical therapy within ICUs in Australia, Japan, Nigeria, Singapore, the United Kingdom, and South Africa. [18][19][20][21][22][23][24] However, it is unclear whether hospital physical therapy or critical care departments utilize these guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…A survey of clinical practice of senior physiotherapists working in Australian ICUs found that physiotherapists commonly provide respiratory physiotherapy interventions during daytime working hours for ventilated patients with CAP, comprising specific positioning to target the affected lung regions, hyperinflation techniques, manual chest wall techniques, and airway suctioning. 15 , 17 These interventions are aimed at improving alveolar ventilation and secretion clearance to optimize pulmonary function and physical recovery and enhance weaning from mechanical ventilation. 15 Despite being considered an essential component of usual care for this ICU patient cohort, 18 , 19 there is limited evidence regarding the efficacy of respiratory physiotherapy for patients who require invasive ventilation in ICU for pneumonia.…”
Section: Introductionmentioning
confidence: 99%